1983
DOI: 10.1017/s0043174500069125
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Bleaching Activity of Norflurazon and Oxyfluorfen

Abstract: The bleaching effects of norflurazon [4-chloro-5-(methylamino)-2-(α,α,α-trifluoro-m-tolyl)-3 (2H)-pyridazinone] and of oxyfluorfen [2-chloro-1-(3-ethoxy-4-nitrophenoxy)-4-(trifluoromethyl) benzene] were compared using the intact microalgaScenedesmus acutusand the fungusPhycomyces blakesleeanus.Under the influence of oxyfluorfen, but not of norflurazon, pigments and membranes were degraded. This activity is typical for oxyfluorfen. Norflurazon prevented carotene synthesis, but did not cause degradation of carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…O método de quantificação das clorofilas a, b e total foi realizado segundo Arnon (1949). Para a determinação dos carotenoides, empregou-se o método de Duke e Kenyon (1986), quantificando os teores do β-caroteno (SANDMANN;BÖRGER, 1983). Para a peroxidação de lipídeos das folhas e raízes, empregou-se o método de quantificação de malonildialdeído (MDA) através da produção de metabólitos reativos a ácido 2-tiobarbitúrico (TBA), baseado nos trabalhos de Heath e Packer (1968) e Buege e Aust (1978).…”
Section: Methodsunclassified
“…O método de quantificação das clorofilas a, b e total foi realizado segundo Arnon (1949). Para a determinação dos carotenoides, empregou-se o método de Duke e Kenyon (1986), quantificando os teores do β-caroteno (SANDMANN;BÖRGER, 1983). Para a peroxidação de lipídeos das folhas e raízes, empregou-se o método de quantificação de malonildialdeído (MDA) através da produção de metabólitos reativos a ácido 2-tiobarbitúrico (TBA), baseado nos trabalhos de Heath e Packer (1968) e Buege e Aust (1978).…”
Section: Methodsunclassified
“…The absorbance of the extracts was measured at 645 and 663 nm, and total chlorophyll concentrations were determined according to Arnon (1949). Carotenoids were extracted from 50 mg of tissue, and total carotenoid concentrations were determined spectrophotometrically according to Sandmann and Böger (1983) with an extinction coefficient of E 445 = 2500 (% w/v).…”
Section: Methodsmentioning
confidence: 99%
“…An increase in the above ground dry matter of winter wheat due to the good weed control from the sethoxydim application, was noted by Bidlack et al (2006) as compared with the untreated control. Qasem and Foy (2006) reported that application of oxadiazon and oxyfluorfen increased shoot dry weight of Syrian marjoram L. Reduction in the chlorophyll content of sunflower, maize, and other plants by oxadiagryl application has been reported (Sandmann and Boger 1983;Nethra and Jagannath 2011).…”
Section: Chlorophyll Content and Morpho-physiological Traitsmentioning
confidence: 99%